2009
DOI: 10.1007/s00125-009-1639-6
|View full text |Cite
|
Sign up to set email alerts
|

Biguanides and thiazolidinediones inhibit stimulated lipolysis in human adipocytes through activation of AMP-activated protein kinase

Abstract: Aims/hypothesis In rodent adipocytes, activated AMPactivated protein kinase reduces the lipolytic rate. As the hypoglycaemic drugs metformin and thiazolidinediones activate this enzyme in rodents, we tested the hypothesis that in addition to their known actions they could have an anti-lipolytic effect in human adipocytes. Methods Adipose tissue was obtained from individuals undergoing plastic surgery. Adipocytes were isolated and incubated with lipolytic agents (isoprenaline, atrial natriuretic peptide) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 51 publications
(89 reference statements)
6
39
2
2
Order By: Relevance
“…Gliclazide had no effect on AMPK activity in 3T3-L1 adipocytes and has been reported to increase plasma adiponectin concentrations in individuals with type 2 diabetes [33], whereas we have shown that metformin is capable of directly stimulating 3T3-L1 adipocyte AMPK activity. This latter observation is in agreement with previous reports in 3T3-L1 adipocytes [34] and isolated human subcutaneous adipocytes stimulated with metformin in vitro [35]. These data argue against the possibility that gliclazide Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Gliclazide had no effect on AMPK activity in 3T3-L1 adipocytes and has been reported to increase plasma adiponectin concentrations in individuals with type 2 diabetes [33], whereas we have shown that metformin is capable of directly stimulating 3T3-L1 adipocyte AMPK activity. This latter observation is in agreement with previous reports in 3T3-L1 adipocytes [34] and isolated human subcutaneous adipocytes stimulated with metformin in vitro [35]. These data argue against the possibility that gliclazide Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, incubation of 3T3-L1 adipocytes with metformin caused a robust stimulation of the equivalent phosphorylation site in mouse HSL (Ser565) and a recent study has demonstrated that ex vivo stimulation of isolated human adipocytes with metformin attenuated isoprenaline and atrial natriuretic peptide (ANP)-stimulated lipolysis without affecting basal lipolysis. Furthermore, metformin stimulated HSL Ser554 phosphorylation under ANPstimulated conditions, although the effect of metformin alone was not reported [35]. One explanation for the discrepancy between the effects observed in isolated or cultured cells and our in vivo study is likely to be the differing concentrations of metformin used in each case and the very different durations of exposure.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Both antagonists prevented the AICAR-induced activation of AMPK, as assessed by the Thr 172 phosphorylation of AMPK ( Figure 7A), indicating that they were active at the concentrations administered. Both compounds were also shown to inhibit the TZD-induced activation of AMPK in other cell types (72,73). However, they did not reverse the effects of TZDs on the release of inflammatory mediators from HASM cells (Figures 7B and 7C).…”
Section: Discussionmentioning
confidence: 93%
“…It has been found in rodent adipocytes that lipolytic and cAMP-elevating stimuli increase AMPK activity, while its activation by AICAR or phenformin strongly reduces isoproterenol-induced lipolysis and fatty acid release (Daval et al 2005). In human adipocytes, b-adrenergic stimulation of lipolysis was found to be down-regulated by concomitant activation of AMPK through TZDs (Bourron et al 2010). Overall, acute AMPK activation in adipose tissue leads to an inhibition of both lipogenesis and lipolysis, whereas it increases fatty acid oxidation and glucose transport (Viollet et al 2009;Daval et al 2006).…”
Section: Ampk Function In Adipose Tissuementioning
confidence: 99%